Konstelasi Sastra Populer Masa Tahun 1950–1968-An sebagai Pengembangan Iptek dalam Kemanusiaan Cerpen “Armini” Karya Motinggo Busye - Roma Kyo Kae Saniro, Andina Meutia Hawa (Puitika, 2023)
The aim of this research is to reveal the intrinsic elements of the short story "Armini" by Motinggo Busye as a representation of the constellation of popular literature during the 1950s to 1960s as a development of science and technology in humanity. This is motivated by Motinggo Busye's works being considered as "light novels" that are thought to present trivial matters. However, in reality, his short stories can provide an overview of the development of science and technology in humanity through the trend of pocket books in his time. "Armini" is one of Motinggo's works that implies a story of humanity, portraying the life of a widow and the negative stigma she must face. This narrative of humanity is the aspect that will be further explored. The research method employed is qualitative research with descriptive analysis. The data acquisition technique used is literature study. To uncover the human values, this research utilizes the theory of human values presented by Nurgiyantoro through the intrinsic elements of characters and characterization previously performed. The results of this study consist of two types of human values as expressed by Nurgiyantoro, namely the relationship between humans and others, and the relationship between humans and themselves. Additionally, the research indicates that Motinggo successfully attempts to break the negative stigma against a widow presented through the elements of characters and characterization in the story. This is a representation of human values towards women. This research contributes theoretically to literary studies, particularly popular literature. Moreover, it provides practical contributions by raising awareness in society to eliminate negative stigmas against women.